2017
DOI: 10.1093/mnras/stx1355
|View full text |Cite
|
Sign up to set email alerts
|

CXO J004318.8+412016, a steady supersoft X-ray source in M 31

Abstract: We obtained an optical spectrum of a star we identify as the optical counterpart of the M31 Chandra source CXO J004318.8+412016, because of prominent emission lines of the Balmer series, of neutral helium, and a He II line at 4686Å. The continuum energy distribution and the spectral characteristics demonstrate the presence of a red giant of K or earlier spectral type, so we concluded that the binary is likely to be a symbiotic system. CXO J004318.8+412016 has been observed in X-rays as a luminous supersoft sou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…One SSS in M31, CXO J004318.8+412016, is estimated to be a WD with a mass of ≥ 1.2M and an accretion rate > 10 −8 M yr −1 and has been reported to be consistent with a post-thermonuclear outburst X-ray behavior of a very rapidly recurring source, possibly with a time of only a few months. No optical outburst has been observed from this source, implying no mass loss (Orio et al 2017). This may be the case for other recurring SSS observed in M31 (Orio et al 2010) and in external galaxies (see catalog by Wang et al 2016).…”
Section: Discussionmentioning
confidence: 83%
“…One SSS in M31, CXO J004318.8+412016, is estimated to be a WD with a mass of ≥ 1.2M and an accretion rate > 10 −8 M yr −1 and has been reported to be consistent with a post-thermonuclear outburst X-ray behavior of a very rapidly recurring source, possibly with a time of only a few months. No optical outburst has been observed from this source, implying no mass loss (Orio et al 2017). This may be the case for other recurring SSS observed in M31 (Orio et al 2010) and in external galaxies (see catalog by Wang et al 2016).…”
Section: Discussionmentioning
confidence: 83%
“…This would be particularly helpful when the number of candidates is high (as is the case for massive photometric surveys -e.g., Corradi et al 2008;Rodríguez-Flores et al 2014) and when spectroscopic follow-up of individual sources is too time expensive to be feasible; and/or when the candidate object is so faint as to render any spectroscopic follow-up impossible, even with the largest available facilities. To give an idea of the exposure times that would be necessary to perform spectroscopic follow-up of SySts in external galaxies, we recall here the case presented by Orio et al (2017). The authors observed CXO J004318.8+412016 in M31 with GMOS-N in long-slit mode (0.75 arcsec slit, B600 grating) for a total of ∼4.6 hours.…”
Section: Discussionmentioning
confidence: 99%
“…spectrum of SMC 3 in Orio et al 2007). There is a symbiotic in M31 that does not have coronal lines of [Fe x] and seems to be a steady nuclear burner, yet it is a steady SSS source (Orio et al 2017). In that system, the plasma density must be higher than 5 ×10 9 cm −3 to avoid forming coronal lines, yet the inclination of the disk and the filling factor the nebular material must be such to allow observing the SSS directly.…”
Section: How Long and Why Do The Nova Wds Remain Hot?mentioning
confidence: 99%
“…Pavlenko et al (2016) also proposed accretion disc variability as the explanation of the variation of the spectral energy distribution and intensity of the emission lines on 1 day timescales. Even if it is not clear whether the secondary does fills its Roche lobe, RS Oph almost certainly hosts an accretion disk, like probably many other symbiotics (see references and discussion in Orio et al 2017).…”
Section: Rs Ophmentioning
confidence: 99%